Cleaner production and environmental aspects of the sugarcane-alcohol segment: Brazilian issues - Alvarenga, Rafael Pazeto; Queiroz, Timóteo Ramos [UNESP]; Nadae, Jeniffer de (My University, 2017)
Current article, inserted within the Cleaner Production (CP) theme, focuses on the sugarcane-alcohol segment in Brazil. The main aspects and environmental impacts of the sector are underscored and demonstrate how CP may contribute towards the solution of its environmental issues. Methodology is foregrounded on a bibliographical review of scientific essays and consultations of organizations dealing with the themes CP Environmental Management and Sugarcane-Alcohol Chain Management. Results show that the sugarcane-alcohol sector causes both positive and negative environmental impacts and CP may be a strategy for the solution of current issues.
Keywords: Cleaner production; Environmental Impacts; Perspectives; Sugarcane